Hypovolemia in Syncope and Orthostatic Intolerance Role of the Renin-Angiotensin System - Jacob, Giris; Robertson, David; Mosqueda-Garcia, Rogelio; Ertl, Andrew C.; Robertson, Rose Marie; Biaggioni, Italo (The American journal of medicine, 1997)
PURPOSE: Orthostatic intolerance is the cause of significant disability in otherwise normal patients. Orthostatic tachycardia is usually the dominant hemodynamic abnormality, but symptoms may include dizziness, visual changes, discomfort in the head or neck, poor concentration, fatigue, palpitations, tremulousness, anxiety and, in some cases, syncope. It is the most common disorder of blood pressure regulation after essential hypertension. There is a predilection for younger rather than older adults and for women more than men. Its cause is unknown; partial sympathetic denervation or hypovolemia has been proposed. METHODS AND MATERIALS: We tested the hypothesis that reduced plasma renin activity, perhaps from defects in sympathetic innervation of the kidney, could underlie a hypovolemia, giving rise to these clinical symptoms. Sixteen patients (14 female, 2 male) ranging in age from 16 to 44 years were studied. Patients were enrolled in the study if they had orthostatic intolerance, together with a raised upright plasma norepinephrine (≥600 pg/mL). Patients underwent a battery of autonomic tests and biochemical determinations. RESULTS: There was a strong positive correlation between the blood volume and plasma renin activity (r = 0.84, P = 0.001). The tachycardic response to upright posture correlated with the severity of the hypovolemia. There was also a correlation between the plasma renin activity measured in these patients and their concomitant plasma aldosterone level. CONCLUSIONS: Hypovolemia occurs commonly in orthostatic intolerance. It is accompanied by an inappropriately low level of plasma renin activity. The degree of abnormality of blood volume correlates closely with the degree of abnormality in plasma renin activity. Taken together, these observations suggest that reduced plasma renin activity may be an important pathophysiologic component of the syndrome of orthostatic intolerance.